Spatial assessment of climate change, water resource management, adaptation and governance in South Africa - Kalumba, Ahmed Mukalazi; Afuye, Gbenga Abayomi; Mazinyo, Sonwabo Perez; Zhou, Leocadia; Adom, Richard Kwame; Simatele, Mulala Danny; Das, Dillip Kumar (Frontiers in Water, 2025)
The study explored the intellectual domain of climate change, water resource management, adaptation, and governance (CCWRM_AG), identifying research hotspots, and proposing solutions to address water scarcity and environmental impacts in South Africa. In total, 1,117 original published studies in BibTeX format were obtained using Web of Science and Scopus databases from 1997 to 2022. The data analyzed on CCWRM_AG includes top-cited articles and the distribution of author keywords, most-cited journals, word cloud, thematic evolution and top author affiliations. The National Integrated Water Information System (NIWIS) database was utilized to monitor and assess the potential for water shortages in South Africa. The study employed geobibliometrics, an integrated approach that combines bibliometric analysis and remote sensing data, to evaluate research trends and monitor dam water levels. The CCWRM_AG field in South Africa is experiencing an 18.98% annual growth in citations per article, with the University of Kwazulu-Natal and the University of Cape Town ranking first with the highest total number of published top articles, indicating their significant influence and associated research centers. Based on the top keyword, climate change and water resource scarcity are central to issues related to drought and water shortage, indicating a hint of the relatedness for further studies. The spatial analysis reveals severe water shortages in the Western Cape province, adversely affecting water quality, agriculture, and livelihoods due to critically low dam levels. The Northern Cape faces water scarcity in its arid lands, while other provinces show relatively stable water availability. The findings of this study can enhance the multifaceted approach that integrates robust water governance infrastructure, regulatory policies, and economic incentives to mitigate water scarcity and environmental impacts.